Optimization of Deep Peak Shaving Methods for Fossil Fuel-Based Power Units Using the Improved Energy Consumption Framework - Zhang, Xing; Zhou, Yunlong (EAI Endorsed Transactions on Energy Web, 2025)
The design optimisation of Fossil Fuel-Based Power Plants is critical for improving energy efficiency and minimising environmental impact, particularly amid the increasing global demand for electricity. Fossil fuel plants are vital for supplying energy needs, but are hindered by fuel inefficiency and emissions. The main aim of this research is to improve the performance of such power plants during peak demand hours and to reduce fuel consumption and emissions. The emphasis is placed on maximizing energy generation, enhancing operational effectiveness, and sustainability. The suggested work combines two advanced optimization methods.
Keywords: Fox Optimization Algorithm; Fossil Fuel-Based Power Units; Demand Response; Thermal Storage; Load Shifting; Peak Demand Management